DNA damage induced by radiation exposure from cardiac catheterization – an analysis in patients and operators. (3rd October 2022) - Ishida, T; Jin, Y; Yaegashi, D; Ishida, M; Sakai, C; Yamaki, T; Nakazato, K; Tashiro, S; Takeishi, Y
Abstract: Background: The biological effects of low-dose radiation from cardiac imaging or intervention remain largely unknown. This study aimed to evaluate the effects of ionized radiation from cardiac catheterization on genomic DNA integrity and inflammatory cytokines in patients and operators. Methods: Peripheral mononuclear cells (MNCs) were isolated from patients (n=52) and operators (n=35) before and after coronary angiography and/or percutaneous coronary intervention. Expression of gammaH2AX, a marker for DNA double-strand breaks, was measured by immunofluorescence. Dicentric chromosomes (DICs), a form of chromosome aberrations, were assayed using a fluorescent in situ hybridization technique. Results: In the patient MNCs, the numbers of gammaH2AX foci and DICs increased after cardiac catheterization by 101±75% and 28±99%, respectively (P<0.05 for both). The mRNA expressions of interleukin (IL)-1α, IL-1β, leukemia inhibitory factor (LIF) and caspase-1 were significantly increased by radiation exposure from cardiac catheterization. The increase in IL-1β was significantly correlated with that of gammaH2AX, but not with dose area product. In the operators, neither gammaH2AX foci nor DICs level was changed, but IL-1β mRNA was significantly increased. Protein expression of IkappaBα was significantly decreased in both groups. Conclusions: DNA damage was increased in the MNCs of patients, but not of operators, who underwent cardiac catheterization. Inflammatory cytokines were increased both in the patients and operators, presumably through activation of NF-kappaB. Further efforts to reduce radiation exposure from cardiac catheterization are necessary both for patients and operators. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Grants-in-Aid for Scientific Research (KAKENHI)